EVALUASI PELAKSANAAN SISTEM SURVEILANS HEALTHCARE ACQUIRED INFECTIONS (HAIS) DI RSU HAJI SURABAYA TAHUN 2020 - Aulia Rosyida; Laura Navika Yamani; Dwiono Mudjianto (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
Healthcare Acquired Infections (HAIs) or nosocomial infections are infections that occur in patients during hospitalization. HAIs are classified into 4 namely Catheter-Associated Urinary Tract Infection, Surgical Site Infection, Ventilator-Associated Pneumonia, and Blood Stream Infection. The purpose of this study is to evaluate the implementation of the HAIs surveillance sistem. The research method used is a descriptive evaluation study with an observational research design. The data sources used are the Reports and dissemination of HAIs Surveillance at RSU Haji Surabaya in 2019-2020. The results showed that HAIs cases at RSU Haji Surabaya in 2020 were 0.03%. The problems in the implementation of HAIs surveillance are the accuracy and completeness of data reports, implementation support facilities, and employee participation in training has not been running optimally, application bundle items are under repair, and job rotation for employees. Conclusion : the implementation of HAIs surveillance activities is in accordance the Regulation of the Peraturan Menteri Kesehatan Republik Indonesia Number 27 of 2017 Tentang  Pedoman Pencegahan  Dan Pengendalian Infeksi  di Fasilitas Pelayanan Kesehatan, but the implementation still running unoptimally, researchers recommend the implementation of reward and punishment activities for surveillance officers as a solution to improve the sistem surveillance.